A Review of Pathophysiology, Clinical Features, and Management Options of COVID-19 Associated Coagulopathy. Issue 6 (June 2021) - Goswami, Julie; MacArthur, Taleen A.; Sridharan, Meera; Pruthi, Rajiv K.; McBane, Robert D.; Witzig, Thomas E.; Park, Myung S.
Abstract : Abstract: There is increasing evidence that novel coronavirus disease 2019 (COVID-19) leads to a significant coagulopathy, a phenomenon termed "COVID-19 associated coagulopathy." COVID-19 has been associated with increased rates of both venous and arterial thromboembolic events, a source of significant morbidity and mortality in this disease. Further evidence suggests a link between the inflammatory response and coagulopathy associated with COVID-19. This presents a unique set of challenges for diagnosis, prevention, and treatment of thrombotic complications. In this review, we summarize and discuss the current literature on laboratory coagulation disruptions associated with COVID-19 and the clinical effects of thromboembolic events including pulmonary embolism, deep vein thrombosis, peripheral arterial thrombosis, and acute ischemic stroke in COVID-19. Endothelial injury and augmented innate immune response are implicated in the development of diffuse macro- and microvascular thrombosis in COVID-19. The pathophysiology of COVID-19 associated coagulopathy is an important determinant of appropriate treatment and monitoring of these complications. We highlight the importance of diagnosis and management of dysregulated coagulation in COVID-19 to improve outcomes in COVID-19 patients with thromboembolic complications.